Bellevue Stratford Hotel
Contains images of the Bellevue Stratford Hotel in Philadelphia. Many views of the exterior are shown, including one of the construction of an addition to the building. Depicts the lobby, wine cellar, and other rooms. Portrays striking employees and guests carrying their own luggage. Crowds are pictured outside the building during the Democratic National Convention and during a fire at the Ritz Carlton Hotel. Also includes exterior views of the former hotel building during its use by the Manufacturers Club.